QUALITATIVE AND QUANTITATIVE PROFILES OF MAJOR MACRONUTRIENT ELEMENTS PRESENT IN ENERGY DRINKS POPULAR IN INDIA USING ICP-MS - Pooja Rana; Arvind Choudhary; Munish Kumar Mishra; Lav Kesharwani; Suchit A. John; Poonam Prakash (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Energy drinks market is increasingly popular in India, where they have been marketed with claims to provide instant boost of energy. They have been equally popular subject of study by food scientists as well where major contents like caffeine, sugars, etc. present in them have been extensively studied by the researchers but less focus has been paid on their elemental composition. The elemental profiling of these drinks becomes a subject of interest also because the consumers consistently consuming these drinks are more susceptible to be negatively impacted by the presence of certain elemental components present in these products, especially because of their high concentrations. Present study investigates the qualitative and quantitative profiles of macro nutrient elements present in energy drinks from ten popular brands in India. Macronutrient elements are required in large amounts for normal and vital functioning of physiological processes in body. In this study, quantitative assessment of 5 such macronutrient elements (Sodium (Na), Magnesium (Mg), Aluminum (Al), Potassium (K), Calcium (Ca)) in energy drink samples of 10 different brands was carried out using microwave assisted acid decomposition and quantitation through ICP-MS instrument which is capable of analyzing several samples rapidly and permitted the identification of multiple metallic elements present in those samples which may be useful for investigations of food frauds in various legal issues. The findings revealed several brands exceeded the permissible limits set by the Food Safety and Standards Authority of India (FSSAI) for key elements, raising significant health concerns.